Réponses

2013-12-06T20:14:53+01:00
Bonsoir,

1)Il faut ajouter des parenthèses au bon endroit :
\left(x+1\right)^2+x+1 =\left(x+1\right)^2+\left(x+1\right) \\=\left(x+1\right)\left(x+1+1\right) = \left(x+1\right)\left(x+2\right)

2)On utilise l'identité remarquable a²-b² = (a-b)(a+b) :
a^2-4+\left(x-2\right)\left(x+1\right) = a^2-2^2+\left(x-2\right)\left(x+1\right) \\
=\left(x+2\right)\left(x-2\right)+\left(x-2\right)\left(x+1\right)\\
= \left(x-2\right)\left(x+2+x+1\right) = \left(x-2\right)\left(2x+3\right)

Si tu as des questions, n'hésite pas! =)